Analysis of the state of immunity in patients with chronic gastritis infected with Helicobacter pylori - Ekaterina V. Mokhonova; V. A. Lapin; D. A. Melentiev; D. V. Novikov; N. V. Neumoina; K. M. Perfilova; M. V. Neumoina; T. A. Troshina; I. V. Shutova; V. V. Novikov (Инфекция и иммунитет, 2022)
Helicobacter pylori is considered an etiological agent of chronic gastritis and a number of other diseases of the gastrointestinal tract. The immune response to H. pylori is characterized by the development of both pro-inflammatory and tolerogenic reactions. Against this background, the possibility of forming autoimmune shifts is also assumed. The purpose of the present study was to conduct a comparative analysis of the state of immunity in patients with chronic gastritis in the exacerbation stage associated with and not associated with H. pylori infection. There were used whole peripheral blood (n = 50) and serum (n = 49) samples from 162 patients with primary chronic gastritis at the exacerbation stage, in which the presence or absence of H. pylori DNA was tested by real-time PCR in gastric juice. In the peripheral blood of patients, the relative content of CD4+FoxP3+ cells (T regulators) and CD4+CD161+ cells (IL-17 producing cells) was evaluated using flow cytofluorometry and monoclonal antibodies method, the level of mRNA FoxP3 and mRNA IL-17A was determined using real time RT-PCR, and the concentration of IL-2 and IL-23 was determined using enzyme immunoassay. It has been shown that in H. pylori-infected patients with chronic gastritis in the exacerbation stage in comparison with patients not infected with H. pylori, the content of CD4+FoxP3+ cells, CD4+CD161+ cells does not change in the blood, also with the level of mRNA FoxP3 and mRNA IL-17A. Since the equilibrium between the populations of Th17 cells and T regulators is modulated by IL-2, which is important for generating the population of T regulators, but inhibits polarization of the immune response towards Th17 cells, we conducted a comparative assessment of the serum IL-2 level in patients with chronic gastritis. All patients showed an increase in IL-2 content in comparison with the norm. In this case, the concentration of IL-2 in the blood of infected H. pylori patients was statistically significantly higher than in H. pylori-uninfected patients. An important regulator of the function of Th17 cells is also IL-23, which induces the differentiation of naive T lymphocytes into Th17 cells involved in inflammatory and autoimmune reactions. In this regard, we determined the level of this cytokine in the blood of patients with chronic gastritis. Multiple increase of IL-23 concentration in comparison with normal level and higher content of IL-23 in H. pylori-infected patients in comparison with uninfected patients were revealed. On the basis of the obtained data, it can be concluded that an increase in the concentration of IL-23 does not exclude the possibility of forming autoimmune shifts with its participation in persons with helicobacter infection, but the issue requires further study.